Interprofessional Oral Health Education Improves Knowledge, Confidence, and Practice for Pediatric Healthcare Providers - Cooper, Devon; Kim, JungSoo; Duderstadt, Karen; Stewart, Ray; Lin, Brent; Alkon, Abbey (Frontiers in Public Health, 2017)
Dental caries is the most prevalent chronic childhood disease in the United States. Dental caries affects the health of 60-90% of school-aged children worldwide. The prevalence of untreated early childhood dental caries is 19% for children two to five years of age in the U.S. Some factors that contribute to the progression of dental caries include socioeconomic status, access to dental care and lack of anticipatory guidance. The prevalence of dental caries remains highest for children from specific ethnic or racial groups, especially those living in underserved areas where there may be limited access to a dentist. Although researchers have acknowledged the various links between oral health and overall systemic health, oral health care is not usually a component of pediatric primary health care. To address this public health crisis and oral health disparity in children, new collaborative efforts among health professionals is critical for dental disease prevention and optimal oral health. This evaluation study focuses on a 10-week interprofessional education (IPE) course on children’s oral health involving dental, osteopathic medical, and nurse practitioner students at the University of California, San Francisco. This study’s goal was to evaluate changes in knowledge, confidence, attitude and clinical practice in children’s oral health of the students completed the course. Thirty-one students participated in the IPE and completed demographic questionnaires and four questionnaires before and after the IPE course: (1) course content knowledge, (2) confidence, (3) attitudes, and (4) clinical practice. Results showed a statistically significant improvement in the overall knowledge of children’s oral health topics, confidence in their ability to provide oral health services, and clinical practice. There was no statistically significant difference in attitude, but there was an upward trend towards positivity. To conclude, this IPE evaluation showed that offering an interprofessional course on children’s oral health to graduate students in dentistry, nursing, and osteopathic medicine can improve their knowledge, confidence, and attitude towards children’s oral health and expand their professional goals to include caring for underserved, minority children.